World inequality report 2018 - Alvaredo, Facundo; Chancel, Lucas; Piketty, Thomas, 1971-; Saez, Emmanuel; Zucman, Gabriel (The Belknap Press of Harvard University Press, 2018)
The World Inequality Report: 2018 is the most authoritative and up-to-date account of global trends in inequality. Researched, compiled, and written by a team of the world's leading economists, it presents, with unrivaled clarity and depth, information and analysis that will be vital to policy makers and scholars everywhere.--